2021
DOI: 10.1007/s00439-020-02252-1
|View full text |Cite
|
Sign up to set email alerts
|

Haploinsufficiency of the HIRA gene located in the 22q11 deletion syndrome region is associated with abnormal neurodevelopment and impaired dendritic outgrowth

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…It regulates neural progenitor proliferation and neurogenesis, and it belongs to the WD40 Repeat (WDR) protein family involved in brain development and neuronal connectivity. Recent studies on HIRA knock-down mouse models demonstrated that its haploinsufficiency is associated with abnormal neurodevelopment and impaired dendritic outgrowth [31]. Other authors analysed hematopoietic cells with specific HIRA deletion in mice and showed that this dramatically reduces bone marrow hematopoietic stem cells (HSCs), resulting in anaemia, thrombocytopenia and lymphocytopenia [32].…”
Section: Discussionmentioning
confidence: 99%
“…It regulates neural progenitor proliferation and neurogenesis, and it belongs to the WD40 Repeat (WDR) protein family involved in brain development and neuronal connectivity. Recent studies on HIRA knock-down mouse models demonstrated that its haploinsufficiency is associated with abnormal neurodevelopment and impaired dendritic outgrowth [31]. Other authors analysed hematopoietic cells with specific HIRA deletion in mice and showed that this dramatically reduces bone marrow hematopoietic stem cells (HSCs), resulting in anaemia, thrombocytopenia and lymphocytopenia [32].…”
Section: Discussionmentioning
confidence: 99%
“…Tbx1 and Dgcr8 are two individual genes within the locus that have garnered attention since they are intolerant to loss of function and have widespread effects on gene regulation; Tbx1 is a transcription factor and Dgcr8 is a protein involved in a microRNA processing complex [52,53]. Numerous murine models targeting genes in the human 22q11.2 locus have been developed to better understand the contribution of single and multiple 22q11.2 genes to developmental, cell-specific, and behavioral deviations relative to wild-type littermates [54][55][56][57][58][59]. For example, Tbx1 heterozygous mice showed significant alterations of myelinated axons in the fimbria, lower mRNA levels of oligodendrocyte-related genes, and postnatal progenitor cells from the subventricular zone produced fewer oligodendrocytes in vitro [60].…”
Section: Genetic Heterogeneity the Value Of Focusing On A Genetically...mentioning
confidence: 99%
“…Furthermore, in bivalent genes that evolve to become transcriptionally active, H3.3 is kept around the TSS and is incorporated into the gene body and in those that become transcriptionally inactive, the H3.3 is lost around the TSS ( Goldberg et al, 2010 ). Additionally, haploinsufficiency of HIRA leads to abnormal defects involved in the regulation of neuronal differentiation and maturation ( Jeanne et al, 2021 ). This places histone variants and their chaperones as important regulators of neuronal development and maturation.…”
Section: Histones Their Chaperones and Their Involvement In Agingmentioning
confidence: 99%
“…The phenotype seen in these patients is very heterogeneous, including heart defects, parathyroid hypoplasia, immune deficiency, and hypocalcemia ( Jeanne et al, 2021 ). Given this, the altered mechanisms that lead to its heterogeneous pathogenesis might depend on the cellular type analyzed, whether it is a neuronal or a hematopoietic stem cell defect.…”
Section: Chromatin Remodelers and Histone Chaperones As Targets In Sy...mentioning
confidence: 99%